Identification of women at high genetic risk of breast cancer through the National Health Service Breast Screening Programme (NHSBSP). Issue 11 (November 1995) - de Silva, D; Gilbert, F; Needham, G; Deans, H; Turnpenny, P; Haites, N
Abstract : Breast cancer is a multifactorial disease with an inherited predisposition being implicated in around 5% of all cases. Using previous epidemiological data assessing risks for the relatives of women with breast cancer, we have identified 154 women (from a screened population of 35, 505) and 289 of their relatives between 50 and 64 years who have more than twice the age related risk of developing breast cancer. This constitutes 1.24% of the breast screening population attending the North East Scotland NHSBSP. For each woman identified to be at high risk, we have found 1.87 female relatives between 50 and 64 years and 1.85 relatives under 50 years also to be at high risk. Around 78% of the women identified with a significant family history of breast or other cancer have attended for counselling about their risks. The breast screening programme can be used to identify women at high risk of breast cancer in order to offer them (and their relatives) access to genetic counselling and appropriate screening.